Model for calcite spherulite formation in organic, clay-rich, lacustrine carbonate shales (Barbalha Formation, Aptian, Araripe Basin, NE Brazil). (June 2021) - Claes, Hannes; Miranda, Tiago; Falcão, Thiago C.; Soete, Jeroen; Mohammadi, Zahra; Zieger, Laura; Erthal, Marcelle M.; Aguillar, Jéssica; Schmatz, Joyce; Busch, Andreas; Swennen, Rudy
Abstract: The formation of carbonate spherulites, recognized as part of the South-Atlantic Pre-Salt reservoir rocks, remains enigmatic. Well-chosen analogues provide insights into depositional and diagenetic conditions and the biotic versus abiotic processes that might influence or even control spherulite growth. Radial fibrous calcite spherulites of the Batateira beds in the Barbalha Formation (Aptian, Araripe, NE Brazil) formed mainly in organic and clay-rich laminite layers as nodules that grew around different nuclei, now represented by, amongst others, micrite and apatite ostracods. They vertically alternate with clays, but also carbonate laminites, which locally also contain spherulites. Characterization of the organic matter content of spherulitites (petrography, total organic carbon, vitrinite reflectance, stable isotopes) reveals TOC's of up to 30% related to the presence of mainly oil-prone alginite next to huminite, inertinite, sporinites and zooclasts. The complex mixture of clays, dominantly autogenic mixed layered illite-montmorrilonite, which alternate with lacustrine carbonates and evaporites, is diagnostic for lakes in a semi-arid environment. The occurrence of gypsum, calcitic alveolar honeycomb spherulite textures, preferential concentration of pyrite at the spherulite-matrix contact and inward spherulite perforations suggest bacterial activity under shallow and evaporitic syn-depositional conditions. Although the Barbalha spherulites formed chemically-driven in a viscous matrix, the microbial influence, mainly as lamalginite in the clayey matrix, is undeniable. The mixed organic-silicate gel catalyzed calcite spherulite formation. The Barbalha spherulites consequently illustrate the complementary influence of clays, organic matter and evaporitic syn-sedimentary conditions. Graphical abstract: Image 1 Highlights: Spherulites formed as concretions in organic, clay-rich lacustrine laminites. The high content of organic matter consists mainly of oil-prone lamalginite. Compaction emphasized the anastomosing character of montmorillonite-illite clays. The paleo-lake water depth of spherulite formation most likely was below 10 m. Microbial and clay mediation were complimentary in the genesis of spherulites.